Pemanfaatan Bio-Economy dari Glycine Max dan Digital Marketing bagi Pengrajin Tempe - Komariyah, Siti; Yuliati, Lilis; Riniati, Riniati (University of Merdeka Malang, 2021)
One of the potentials Jambearum village is from the tempe production which is located in Puger, Jember regency. This potential has the opportunity to be developed into a center for SMEs, because several businesses have joined the